The Impact of Islamic Monetary Instruments and Islamic Social Funds on Indonesia’s Economic Growth - Khairina Tambunan; Andri Soemitra; Isnaini Harahap (Politeknik Siber Cerdika Internasional, 2026)
Background: Indonesia still faces economic development disparities, making it important to examine whether inclusive growth can be achieved through Islamic monetary instruments and Islamic social funds. This study employs Gross Domestic Product (LGDP), Bank Indonesia Sharia Certificates (LSBIS), Bank Indonesia Sharia Deposit Facilities (LFASBIS), and Zakat, Infaq, and Sadaqah (LZIS) as variables. Objective: This study aims to explore how Islamic monetary instruments and Islamic social funds affect Indonesia’s economic growth. Methods: A quantitative explanatory approach was employed using monthly data from 2017–2023 obtained from BPS, Bank Indonesia, and BAZNAS. Data were analyzed using the Vector Error Correction Model (VECM), supported by the Augmented Dickey–Fuller (ADF), Johansen cointegration, Granger causality, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD) tests through EViews 11. Results: The results show sparse and predominantly unidirectional Granger causality relationships. Based on the short-run and long-run coefficients, the Islamic variables do not have a significant influence on LGDP in the short run, while LSBIS, LZIS, and LFASBIS significantly contribute to economic growth in the long run. The FEVD results indicate that LSBIS accounts for the highest percentage of variance in LGDP (23.30%), followed by LZIS (2.16%) and LFASBIS, which contributes only 0.16%. Conclusion: The results indicate that Islamic monetary instruments and Islamic social funds have weak short-term effects but strong long-run relationships with economic growth, suggesting a gradual adjustment process in Indonesia’s Islamic economic transmission mechanism, as well as the need for timely policy coordination to foster more inclusive and sustainable growth.